Understanding and Assessing the Book of Modern Political Analysis: Innovations and Dilemmas - Mohammad abdolahpour chenari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this paper is, in particular, to understand and evaluate Robert Dahl and Brackner's book, modern political analysis and in general, to provide a framework for analyzing a text. Today, the conventional way of examining a text with false assumptions, which actually lead to a lack of understanding and evaluation, is to presuppose definitions of understanding and evaluation, attention to semantic dimensions, and emphasis on face and content evaluation. But, is it really possible to evaluate without understanding the work? The main reasoning behind this article is that the conditions for the possibility of understanding and evaluating a piece of work, based on this assumption, are that understanding and evaluation are inextricably bound. The context of understanding requires the return of the text to the historical context and the context of the evaluation involves the propositional content. The result of the application of this interconnectedness is that the work has been written in the political atmosphere of "democracy" and "behaviorist" science. The verbs contained in the speech initially confirm the behavioral-oriented monistic methodology, then change into pluralistic affiliation. An increasing propositional content represents innovation in the thematic, political, and methodological context. Decreasing propositional content points to problems in the methodological domain of political sciences. For example, it is not able to provide a valid argument about how to obtain normative propositions from the empirical methods of studying the historical and metaphysical values. Therefore, the understanding and appraisal of political phenomena require Robert Dahl's methodological adjustments.